Penguatan Karakter Islami melalui Festival Anak Shaleh di TPA Cot Mee - Ulfi Hayati (LSM Catimore dan Sahabat, 2026)
The Shaleh Children's Festival is a competition that serves as a basis for character building in children as motivation in the learning environment. This article aims to increase understanding of Islamic teachings and shape Islamic character as a foundation for community life. Using qualitative analysis methods through interviews, observation, and documentation, accompanied by planning, implementation, and evaluation, the Shaleh Children's Festival was carried out well, safely, smoothly, and successfully. Through Qur'an reading and writing (BTQ) lessons, which consist of memorizing short surahs, the obligatory attributes of Allah and His Messenger, the pillars of faith and Islam, the names of the prophets and messengers, the duties of angels, the call to prayer, and speeches, the Gema Islam activity became a forum for children at the Mabna-Uthulab and Izzatul Ilmi TPA to develop religious attitudes, integrity, and social awareness.